BST Algorithm for Duplicate Elimination in Data Warehouse - Pahwa, Payal; Chhabra, Rashmi (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Data warehousing is an emerging technology and has proved to be very important for an organization. Today every business organization needs accurate and large amount of information to make proper decisions. For taking the business decisions the data should be of good quality. To improve the data quality data cleansing is needed. Data cleansing is fundamental to warehouse data reliability, and to data warehousing success. There are various methods for datacleansing. This paper addresses issues related data cleaning. We focus on the detection of duplicate records. Also anefficient algorithm for data cleaning is proposed. A review of data cleansing methods and comparison between them is presented.